A new Dinapsis species from the Central African Republic (Hymenoptera, Megalyridae, Dinapsini) - Shaw, Scott Richard; van Noort, Simon (Zootaxa, 2009)
A new species of megalyrid wasp, Dinapsis centralis Shaw and van Noort sp. nov. from the Central African Republic is described and illustrated. The new species is contrasted with other described species of Dinapsis. An online key to Dinapsis species is available at: http://www.waspweb.org/Megalyroidea/Megalyridae/Keys/index.htm. This represents the first record of any megalyrid species from the Central African Republic and the northernmost confirmed distribution of Dinapsis in the Afrotropical region. The taxonomic history, distribution, biogeography and biology of Megalyridae are discussed.